Letter (copy) : Assistance to Republican Spaniards - Tewson, Vincent
1949-05-10 038-0006-001 Secretary's. VT/EK/318. 10th May, 1949. The Lady Layton, Chairman, National Joint Committee for Spanish Relief, 39, Victoria Street, London, S.W.1. Dear Lady Layton, Assistance to Republican Spaniards. I saw your letter of the 4th April upon my return from the States just after Easter. Very many thanks for the information you send. You will appreciate, of course, that our connection with the work of the Joint Committee was specifically in regard to the Basque children with many of whom my wife and I still have close contact. On the point you raise about the more general work, I hardly think that the General Council would be inclined to take over the P.T.O. 292/946/38/6(I)